Who are them? Identifying and characterizing councilors in Brazil (2000-2016) - Silva, Bruno Souza da; Dantas, Humberto (Universidade Estadual Paulista / UNESP, 2018)
Councilors are the largest share of politicians in Brazil, however, we do not know much about them. This affirmation can be exemplified, based on the municipal elections from 2000 to 2016, by averages of 380,597 candidates disputing 56,146 places. Initially it seems that such elections mobilize all parties and thousands of postulants, symbolizing a representative democracy that stimulates participation. Thus, we have a political framework marked by continuous party fragmentation and competitive elections. But who are the councilmen? Locally, parties tend not to perform parliamentary co-ordination functions, which are characteristically expected to be held in Parliament. This argument reinforces the fact that 85% of the chambers have between 9 and 11 councilmen. In this configuration, it can be deduced that the main actors are the councilors themselves, not the parties. It is then necessary to characterize who these agents are and whether they remain in the elections. In consideration that the research problem is who are the candidates who win elections and, consequently, if the elect vary or there is a marked permanence, the central hypothesis is that the entrance in the municipal Legislative is more restricted than the great volume of applications would suggest and this is due to the fact that the entry is concentrated in the hands of a few local politicians.